Thirzepatide. A novelty in the treatment of obesity - literature review - Wiśniewska, Katarzyna; Gmitrzuk, Julita; Malinka, Zuzanna; Jachymek, Anna; Opatowska, Martyna; Jakubiec, Joanna; Kucharski, Tomasz; Piotrowska, Marta (Quality in Sport, 2024)
Introduction Obesity results from a complex interplay of environmental, genetic, and behavioral factors, making it challenging to treat. Globally, the prevalence of obesity has tripled over the past fifty years. The WHO reports that 60% of Europeans are overweight or obese mainly due to sedentary lifestyles and poor dietary habits. Effective treatment of obesity requires a combination of lifestyle modifications, including diet and physical activity, and pharmacological interventions. In 2023 a new drug - tirzepatide was registered. The purpose of this study is to discuss the mechanisms of action of tirzepatide, its safety and its effectiveness in body mass reduction, as well as its comparison with other available drug. Aim of the Study The purpose of this study is to provide a comprehensive review of current treatments for obesity, with particular emphasis on the role of recent development in pharmacotherapy - the introduction of tirzeptide. The study aims to discuss the mechanisms of action of tirzepatide, its safety and its effectiveness in body mass reduction, as well as its comparison with semaglutide. Materials and methods A review of the literature collected in the PubMed database was performed to gather information found under the keywords: tirzepatide, obesity, obesity treatment Conclusions Studies have shown that tirzepatide is more effective in weight loss than placebo and semaglutide, and reduces cardiovascular and metabolic risks. Furthermore, it does not increase the risk of serious adverse events or mortality compared to placebo, and its main side effects manifested by gastrointestinal symptoms are described as mild to moderate.